White matter alterations of the corticospinal tract in adults born very preterm and/or with very low birth weight. Issue 1 (21st October 2015) - Jurcoane, Alina; Daamen, Marcel; Scheef, Lukas; G. Bäuml, Josef; Meng, Chun; M. Wohlschläger, Afra; Sorg, Christian; Busch, Barbara; Baumann, Nicole; Wolke, Dieter; Bartmann, Peter; Hattingen, Elke; et al.
Abstract: White matter (WM) injury, either visible on conventional magnetic resonance images (MRI) or measurable by diffusion tensor imaging (DTI), is frequent in preterm born individuals and often affects the corticospinal tract (CST). The relation between visible and invisible white mater alterations in the reconstructed CST of preterm subjects has so far been studied in infants, children and up to adolescence. Therefore, we probabilistically tracked the CST in 53 term‐born and 56 very preterm and/or low birth weight (VP/VLBW,  < 32 weeks of gestation and/or birth weight < 1, 500 g) adults (mean age 26 years) and compared their DTI parameters (axial, radial, mean diffusivity—AD, RD, MD, fractional anisotropy—FA) in the whole CST and slice‐wise along the CST. Additionally, we used the automatic, tract‐based‐spatial‐statistics (TBSS) as an alternative to tractography. We compared control and VP/VLBW and subgroups with and without CST WM lesions visible on conventional MRI. Compared to controls, VP/VLBW subjects had significantly higher diffusivity (AD, RD, MD) in the whole CST, slice‐wise along the CST, and in multiple regions along the TBSS skeleton. VP/VLBW subjects also had significantly lower (TBSS) and higher (tractography) FA in regions along the CST, but no different mean FA in the tracked CST as a whole. Diffusion changes were weaker, but remained significant for both, tractography and TBSS, when excluding subjects with visible CST lesions. Chronic CST injury persists in VP/VLBW adults even in the absence of visible WM lesions, indicating long‐term structural WM changes induced by premature birth. Hum Brain Mapp 37:289–299, 2016 . ©2015 Wiley Periodicals, Inc.